Process Modeling and Simulation of the Radiation in the Electric Arc Furnace. Issue 4 (12th February 2018) - Meier, Thomas; Gandt, Karima; Hay, Thomas; Echterhof, Thomas
Abstract : In this paper, an approach to the enhancement of a dynamic process simulation model of an electric arc furnace (EAF) is described by improving the modeling and simulation of the heat transfer especially by radiation within the EAF. The presented work is a continuation of the work of Logar, Dovžan, and Škrjanc on modeling the heat and mass transfer and the thermochemistry in an EAF. The modeling and simulation of the heat transfer within the EAF is improved by including the electrode in the model and considering the convective and radiative heat transfer to and from the electrodes, for example, by modeling the surface of the electrodes as a radiative surface. Furthermore, the modeling of the melting geometry is improved and implemented in the model in a way to allow for more geometric variability of the scrap meltdown simulation. As a consequence, the view factor calculation within the model is implemented a new way, allowing for a fast and efficient matrix calculation. Finally, the modeling of the thermal radiation of the gas phase is revised to include gas species previously added to the model and to consider emissivity, absorptivity and transmittance of the gas phase as well as the dust load. Abstract : An EAF process model is enhanced by improving the handling of the electrodes as a separate phase partaking in the heat transfer within the EAF as well as by improving the scrap meltdown modeling and the modeling of the thermal radiation of the gas phase.